The Role of AVROS in the Recruitment and Distribution of Plantation Labor in East Sumatra during the Colonial Period, 1910–1942 - M. Faisal Ramadhan; Achiriah Achiriah (Local History & Heritage, 2026)
This study aims to analyze the role of the Algemeene Vereeniging van Rubberplanters ter Oostkust van Sumatra (AVROS) in the recruitment and distribution system of plantation labor in East Sumatra during the period 1910–1942. Employing the historical method—comprising heuristics, source criticism, interpretation, and historiography—this study is further supported by the analytical framework of colonial capitalism and labor control theory. The findings reveal that AVROS functioned not merely as an employers’ association, but as an institution that actively organized, regulated, and distributed labor through centralized and bureaucratic mechanisms. While this system ensured efficiency in fulfilling plantation labor demands, it simultaneously reinforced asymmetrical power relations between employers and workers. Through instruments such as labor contracts, mobility control, and regulated labor distribution, AVROS contributed to the maintenance of an exploitative colonial labor structure. The study argues that plantation labor systems under colonial rule were shaped not only by economic imperatives but also by institutionalized mechanisms of social control. These findings advance the scholarship on colonial capitalism by demonstrating the inseparability of economic practices and coercive labor governance, while offering important insights into the structural dynamics of labor exploitation in colonial plantation economies.